Pengaturan Terhadap Arogansi Pengendara Mobil Pribadi Di Jakarta - Ayu Safa Mutiara; Agnes Cynthia; Muhammad Reza; Sefriyan Reynaldi; Radhiya Nauval Adli Pratama; Mulyadi Mulyadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Traffic jams in Jakarta are indeed very severe, even Jakarta was once the city with the worst traffic jams in the world. So it is not uncommon for violations to occur when driving because of the dense and murky traffic conditions in Jakarta. Such as running through a red light, passing through a route that is not supposed to be, and some even intimidate other road users. This is done in order to get priority on the streets. This research is dedicated to finding out the regulation of driver arrogance in Indonesia, and to find out why the phenomenon of private car driver arrogance in Jakarta is increasingly prevalent. The research was carried out using normative juridical methods based on laws and regulations, related books, and legal research. It can be said, using a method through a statutory approach (statute approach) and a case approach (case approach). It is proven that there are still many cases of arrogance being committed. In Jakarta there are still arrogant private car drivers. Whereas in driving, drivers should have ethics in driving on the road. Most perpetrators of arrogance who dare to break the law on this highway are dominated by luxury car drivers. This is due to social hierarchies that make them feel higher than other drivers.